In vitro evaluation of the antileishmanial activity of methanolic extract of seven medicinal plants - Rojas, Juan P (2012)
The purpose of this study was to determine the in vitro antileishmanial activity of the methanol extract of seven medicinal plants, and the effect on nitric oxide production in macrophages. The extracts in concentration of 250 μg/mL were tested against intracellular amastigotes. Mouse peritoneal macrophages infected with Leishmania peruviana were stained with Giemsa and examined microscopically to determine the parasite load by 100 macrophages. Nitric oxide was determined indirectly by its conversion to nitrite. Piper aduncum (matico) reduced the survival of amastigotes to 51,30% (p < 0,001), also observed a slight effect of Eucalyptus globulus (eucalyptus) and Punica granatum (pomegranate), while Annona cherimola (custard), Annona muricata (graviola) and Origanum vulgare (oregano) were inactive. Nitric oxide production by macrophages was increased significantly by the effect of Annona cherimola, which led to concentration of 13,50 ± 1,50 μM compared with 4,90 ± 0,10 μM in the control (p < 0,001). It also produced significant increase of nitrite with Origanum vulgare (p < 0,05) and Punica granatum (p < 0,01). Was conclude that Piper aduncum, Eucalyptus globulus and Punica granatum showed moderate antileishmanial effect in vitro, and the production of nitric oxide is one of the possible mechanisms of action for Punica granatum.